Respuesta :
we have
[tex]g(x)=(x^{2}+3x-4)( x^{2}-4x+29)[/tex]
To find the roots of g(x)
Find the roots of the first term and then find the roots of the second term
Step 1
Find the roots of the first term
[tex](x^{2}+3x-4)=0[/tex]
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex](x^{2}+3x)=4[/tex]
Complete the square. Remember to balance the equation by adding the same constants to each side
[tex](x^{2}+3x+1.5^{2})=4+1.5^{2}[/tex]
[tex](x^{2}+3x+1.5^{2})=6.25[/tex]
Rewrite as perfect squares
[tex](x+1.5)^{2}=6.25[/tex]
Square root both sides
[tex](x+1.5)=(+/-)2.5[/tex]
[tex]x=-1.5(+/-)2.5[/tex]
[tex]x=-1.5+2.5=1[/tex]
[tex]x=-1.5-2.5=-4[/tex]
so the factored form of the first term is
[tex](x^{2}+3x-4)=(x-1)(x+4)[/tex]
Step 2
Find the roots of the second term
[tex](x^{2}-4x+29)=0[/tex]
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex](x^{2}-4x)=-29[/tex]
Complete the square. Remember to balance the equation by adding the same constants to each side
[tex](x^{2}-4x+4)=-29+4[/tex]
[tex](x^{2}-4x+4)=-25[/tex]
Rewrite as perfect squares
[tex](x-2)^{2}=-25[/tex]
Remember that
[tex]i=\sqrt{-1}[/tex]
Square root both sides
[tex](x-2)=(+/-)5i[/tex]
[tex]x=2(+/-)5i[/tex]
[tex]x=2+5i[/tex]
[tex]x=2-5i[/tex]
so the factored form of the second term is
[tex](x^{2}-4x+29)=(x-(2+5i))(x-(2-5i))[/tex]
Step 3
Substitute the factored form of the first and second term in g(x)
[tex]g(x)=(x-1)(x+4)(x-(2+5i))(x-(2-5i))[/tex]
therefore
the answer is
the roots are
[tex]x1=1\\x2=-4\\x3=(2+5i)\\x4=(2-5i)[/tex]